Intercropping enhances litter accumulation and nutrient return in walnut plantations: a seasonal analysis - Muhammad Asghar Ali; Weiyi Yang; Xiulin Zhu; Jinrui Xue; Fozia Dost Muhammad; Qi Lu; Shuaijie Lu; Jingyan Wang; Wei Gong (Agroforestry Systems, 2026)

Optimizing organic fertilizer nitrogen substitution to enhance growth, nutrient uptake, and use efficiency in Zanthoxylum armatum - Fozia Dost Muhammad; Yuxin Xie; Yuanjia Gong; Muhammad Asghar Ali; Shuaijie Lu; Wenkai Hui; Jingyan Wang; Wei Gong (Soil and Tillage Research, 2026)

Oyster aquaculture enhances sedimentary nitrogen removal in a subtropical estuary - Jian Zhang; Hao Jiang; Yanping Li; Wenshi Zhang; Wenlu Lan; Xin Luo; Dost Muhammad; Shahzad Afzal; Ke Pan (Regional Studies in Marine Science, 2026)

Farmyard manure mineralization: field and laboratory insights into manure placement depth and mulching strategies for sustainable maize production - Sarmad Iqbal; Ahmad Khan; Gulzar Ahmad; Habib Akbar; Dost Muhammad (Plant and Soil, 2026)

Effect of Various Nitrogen and Sulfur Sources on Maize-Wheat Yield and N:S Uptakes Under Two Different Climatic Conditions - Ibad Ullah; Dost Muhammad; Maria Musarat (Agricultural Research, 2025)

Maize productivity and nutrient status in response to crop residue mineralization with beneficial microbes under various tillage practices - Haris Khan; Ahmad Khan; Sajid Khan; Anjum Anjum; Habib Akbar; Dost Muhammad (Soil and Tillage Research, 2024)

Technology advancement and international law in marine policy, challenges, solutions and future prospective - Muhammad Bilawal Khaskheli; Shumin Wang; Xin Zhang; Imran Haider Shamsi; Chenghuan Shen; Sanober Rasheed; Zakir Ibrahim; Dost Muhammad Baloch (Frontiers in Marine Science, 2023)
The use of technology and international law in marine policy is becoming increasingly vital as we seek to address the challenges facing our oceans. Technology has revolutionized our ability to monitor, understand, and manage marine ecosystems, providing valuable tools for data collection, analysis, and decision-making. International law, ocean governance ensuring marine environment represented by the frameworks such as the United Nations Convention on the Law of the Sea (UNCLOS), plays a crucial role in governing the use of technology and establishing guidelines for the sustainable management of marine resources. This paper explores the intersection of technology and international law in marine policy, highlighting the transformative impact of technology on our understanding of the oceans and the legal frameworks that shape our approach to marine conservation. It examines the benefits of technology in enabling evidence-based decision-making and fostering international collaboration, while also addressing the legal and regulatory complexities that arise. The paper emphasizes the need for ongoing dialogue and the development of international legal frameworks to adapt to emerging technologies and discourse ethical considerations, and by harnessing the power of technology and international law, we can work towards effective marine policies that ensure the conservation and sustainable use of our oceans for future generations.

Effect of Various Nitrogen Sources at Various Sulfur Levels on Maize–Wheat Yield and N/S Uptake under Different Climatic Conditions - Ibad Ullah; Dost Muhammad; Maria Mussarat (Journal of Plant Growth Regulation, 2023)

Correction to: Water resources of Balochistan, Pakistan—a review - Malik Muhammad Akhtar; Abida Dost Mohammad; Muhsan Ehsan; Rabia Akhtar; Jalil ur Rehman; Zaira Manzoor (Arabian Journal of Geosciences, 2021)

Optimizing Phosphorus Levels in Wheat Grown in a Calcareous Soil with the Use of Adsorption Isotherm Models - Muhammad Farhan Saeed; Aftab Jamal; Dost Muhammad; Ghulam Mustafa Shah; Hafiz Faiq Bakhat; Iftikhar Ahmad; Sajjad Ali; Fahid Ihsan; Jingkuan Wang (Journal of Soil Science and Plant Nutrition, 2021)

Water resources of Balochistan, Pakistan—a review - Malik Muhammad Akhtar; Abida Dost Mohammad; Muhsan Ehsan; Rabia Akhtar; Jalil ur Rehman; Zaira Manzoor (Arabian Journal of Geosciences, 2021)

Dynamics of AB-DTPA-extractable Zn in high and low limed calcareous soils amended with biochar and farmyard and poultry manures - Abida Saleem; Dost Muhammad; Mumtaz Khan; Qudrat Ullah Khan; Muhammad Rizwan; Salma Shaheen; Hamza Noor; Shiza Gul; Muhammad Daud Khan; Shafaqat Ali (Arabian Journal of Geosciences, 2020)

Propagation of the Multi-Scalar Aggregative Standardized Precipitation Temperature Index and its Application - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Dost Muhammad Khan; Rizwan Niaz; Elsayed Elsherbini Elashkar; Alaa Mohamd Shoukry (Water Resources Management, 2020)

Appraisal for site specific plant nutrient management through spatial variability and mapping in hilly areas of northern Pakistan - Munir Ahmad; Dost Muhammad; Maria Mussarat; Abid Ali Khan; Shah Faisal Khan; Muhammad Waqas Javed (Journal of Soils and Sediments, 2017)

Missense mutations (p.H371Y, p.D438Y) in gene CHEK2 are associated with breast cancer risk in women of Balochistan origin - Abdul Hameed Baloch; Shakeela Daud; Nafeesa Raheem; Muhammad Luqman; Adeel Ahmad; Abdul Rehman; Jameela Shuja; Saeeda Rasheed; Akhtar Ali; Naseebullah Kakar; Hafiz Khush Naseeb; Mohammad Alam Mengal; et al. (Molecular Biology Reports, 2014)

An Alu repeat-mediated genomic GCNT2 deletion underlies congenital cataracts and adult i blood group - Guntram Borck; Naseebullah Kakar; Jochen Hoch; Katrin Friedrich; Jan Freudenberg; Gudrun Nürnberg; Rüstem Yilmaz; Shakeela Daud; Dost Muhammad Baloch; Peter Nürnberg; Johannes Oldenburg; Jamil Ahmad; et al. (Human Genetics, 2012)